An eCIRP inhibitor attenuates fibrosis and ferroptosis in ischemia and reperfusion induced chronic kidney disease - Fangming Zhang; Zhijian Hu; Asha Jacob; Max Brenner; Ping Wang (Molecular Medicine)
Abstract Background Chronic kidney disease (CKD) is a leading cause of death in the United States, and renal fibrosis represents a pathologic hallmark of CKD. Extracellular cold-inducible RNA-binding protein (eCIRP) is a stress response protein involved in acute inflammation, tissue injury and regulated cell death. However, the role of eCIRP in chronic inflammation and tissue injury has not been elucidated. We hypothesize that eCIRP is involved in renal ischemia/reperfusion (RIR)-induced CKD and that C23, an antagonist to eCIRP, is beneficial in attenuating renal fibrosis and ferroptosis in RIR-induced CKD. Methods C57BL/6 (WT) or CIRP−/− mice underwent renal injury with total blockage of blood perfusion by clamping bilateral renal pedicles for 28 min. In the WT mice at the time of reperfusion, they were treated with C23 (8 mg/kg) or vehicle. Blood and kidneys were harvested for further analysis at 21 days thereafter. In a separate cohort, mice underwent bilateral RIR and treatment with C23 or vehicle and were then subjected to left nephrectomy 72 h thereafter. Mice were then monitored for additional 19 days, and glomerular filtration rate (GFR) was assessed using a noninvasive transcutaneous method. Results In the RIR-induced CKD, CIRP−/− mice showed decreased collagen deposition, fibronectin staining, and renal injury as compared to the WT mice. Administration of C23 ameliorated renal fibrosis by decreasing the expression of active TGF-β1, α-SMA, collagen deposition, fibronectin and macrophage infiltration to the kidneys. Furthermore, intervention with C23 significantly decreased renal ferroptosis by reducing iron accumulation, increasing the expression of glutathione peroxidase 4 (GPX4) and lipid peroxidation in the kidneys of RIR-induced CKD mice. Treatment with C23 also attenuated BUN and creatinine. Finally, GFR was significantly decreased in RIR mice with left nephrectomy and C23 treatment partially prevented their decrease. Conclusion Our data show that eCIRP plays an important role in RIR-induced CKD. Treatment with C23 decreased renal inflammation, alleviated chronic renal injury and fibrosis, and inhibited ferroptosis in the RIR-induced CKD mice.